Comparative classification of coordinating sentences in the English and Azerbaijani languages - Əliyeva Sevinc Akif qızı (Scientific Research and Experimental Development, 2024)
Language is the most important means of communication between people. Knowing a foreign language is very necessary in our modern and globalized world. It is not for nothing that they say that the more languages ​​you know, the more you are a person. Today, our youth, who understand the importance of this, are eager to learn more languages. Since sentences are the most optimal means of communication in every language, it is important to examine them as the main communicative unit and classify them according to their meaning and structure. Since the classification of the sentence according to its structure has a dominant character, excluding word combinations, the science of syntax deals with the study of the structural features of the sentence from beginning to end. The sentence structure is simple and compound. A simple sentence is formed from words, word combinations, and a compound sentence is formed from simple sentences. A simple sentence has one predicative center, and a compound sentence has two or more predicative centers. Since the components of a compound sentence do not have meaning independence, intonation exhaustion, it is not considered a sentence or is conditionally called a "sentence".